PENGARUH TERPAAN BERITA PELECEHAN SEKSUAL DI PONDOK PESANTREN PADA TELEVISI TERHADAP PERUBAHAN MINAT MASYARAKAT MEMILIH LEMBAGA PENDIDIKAN ANAK (Survei Pada Orang Tua Di Kelurahan Pabuaran Mekar). - Farizky Ramadhan Anandi, (2023)
For the sake of educating the nation's life for the next generation, of course parents want the best educational institutions for their children and one of the institutions that offer complete education both academically and spiritually is Islamic boarding schools. However, lately there has been widespread news in various media and one of them is television which shows cases of sexual harassment that occurred in Islamic boarding schools, causing uproar in the community so that this amount of news has triggered a potential change in public interest in choosing Islamic boarding schools as a destination for children's education. This study aims to measure the relationship between exposure to news of sexual harassment among Islamic boarding schools on television on changes in people's interest in choosing a child's educational institution. The theory used in this study is Cultivation theory by George Gerbner to provide guidance regarding how exposure to news broadcasts has a certain effect on audiences, the research methodology used in this study is a quantitative approach with explanatory research and survey research methods. The population chosen in this study was the number of households in the Pabuaran Mekar Village with a sample of 100 respondents. The results of the study stated that news of sexual harassment in Islamic boarding schools had an impact of 63.9% on changes in people's interest in choosing children's educational institutions. The hypothesis test also shows the rejection of Ho and acceptance of Ha. Thus, it can be concluded that there is a relationship between exposure to information regarding cases of sexual harassment in Islamic boarding schools and changes in interest in choosing children's educational institutions in the community in Pabuaran Mekar Village.